Spiritual nursing care: A concept analysis - Lydia V. Monareng (AOSIS, 2012)
Although the concept 'spiritual nursing care' has its roots in the history of the nursing profession, many nurses in practice have difficulty integrating the concept into practice. There is an ongoing debate in the empirical literature about its definition, clarity and application in nursing practice. The study aimed to develop an operational definition of the concept and its application in clinical practice. A qualitative study was conducted to explore and describe how professional nurses render spiritual nursing care. A purposive sampling method was used to recruit the sample. Individual and focus group interviews were audio-taped and transcribed verbatim. Trustworthiness was ensured through strategies of truth value, applicability, consistency and neutrality. Data were analysed using the NUD*IST power version 4 software, constant comparison, open, axial and selective coding. Tech's eight steps of analysis were also used, which led to the emergence of themes, categories and sub-categories. Concept analysis was conducted through a comprehensive literature review and as a result 'caring presence' was identified as the core variable from which all the other characteristics of spiritual nursing care arise. An operational definition of spiritual nursing care based on the findings was that humane care is demonstrated by showing caring presence, respect and concern for meeting the needs not only of the body and mind of patients, but also their spiritual needs of hope and meaning in the midst of health crisis, which demand equal attention for optimal care from both religious and nonreligious nurses.